2014
DOI: 10.3390/ijms150915891
|View full text |Cite
|
Sign up to set email alerts
|

Small Engine, Big Power: MicroRNAs as Regulators of Cardiac Diseases and Regeneration

Abstract: Cardiac diseases are the predominant cause of human mortality in the United States and around the world. MicroRNAs (miRNAs) are small non-coding RNAs that have been shown to modulate a wide range of biological functions under various pathophysiological conditions. miRNAs alter target expression by post-transcriptional regulation of gene expression. Numerous studies have implicated specific miRNAs in cardiovascular development, pathology, regeneration and repair. These observations suggest that miRNAs are poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 140 publications
1
43
0
Order By: Relevance
“…MicroRNAs (miRNAs) play key regulatory role in diverse biological process during development, physiology and disease, including HF [16]. miRNA target prediction analysis identified that ELAVL1 harbors complementary binding sites for several miRNAs including miRNA-9 (Position 675–682 and 2818–2825).…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) play key regulatory role in diverse biological process during development, physiology and disease, including HF [16]. miRNA target prediction analysis identified that ELAVL1 harbors complementary binding sites for several miRNAs including miRNA-9 (Position 675–682 and 2818–2825).…”
Section: Resultsmentioning
confidence: 99%
“…In the pathological form, the size of the heart initially increases to compensate for the damage to cardiac tissue, but later leads to a decline in left ventricular function [52]. Pathological hypertrophy has been extensively studied and reviewed in relation to miRNAs that are present in the heart [18, 43]. To understand the specific role of miRNAs in cardiac hypertrophy, van Rooij et al have reported the first microarray analysis data using two different animal models of pathological cardiac hypertrophy.…”
Section: Mirnas In Cardiovascular Diseasesmentioning
confidence: 99%
“…Recently, micro ribonucleic acids (miR) (∼20-22 nucleotide small RNAs) have elicited substantial interest as regulators of and therapeutic targets for HF (6). MiR dysregulation after cardiac injury has been implicated in several biological processes involved in cardiovascular diseases (7,8).…”
Section: Introductionmentioning
confidence: 99%